Stability analysis in chilli (Capsicum annuum L.) under open and mahogany (Swietenia mahagoni L.) based agroforestry system - A N Dey, L S Datta (Journal of Spices and Aromatic Crops, 2009)
Eight chilli genotypes (Capsicum annuum) were evaluated for yield and yield parameters underopen and mahogany (Swietenia mahagoni) based agroforestry system for stability analysis atnorthern West Bengal. Genotype and environment interactions for plant height, primaryand secondary branches, plant spread, stem girth, fruit length and diameter and yield weresignificant indicating differential response of genotypes under different environments.Significant linear and nonlinear components of genotype - environments were recorded forplant height, fruit length and yield. The chilli genotype CA-5 may be adopted for cultivationunder favourable (open) conditions in view of its stabilty. Though CA-12 and Bhaghyalakshmirecorded lower yield than the mean yield, these two genotypes were stable. Bhaghyalakshmiwas stable under open and agroforestry condition and CA-12 was specifically adapted underagroforestry condition.